DINAMIKA PARTISIPASI KOMUNITAS DALAM PENDIDIKAN LUAR SEKOLAH: Kasus Kampung Pendidikan Mandhala Senom - Mohammad Bustanol Husein; Imami Eka Aprillia; Erina Saputri; Rina Nur Azizah (Journal Publicuho, 2024)
The aim of this research is to determine the dynamics of community participation in out-of-school education in the case of the Mandhala Senom Education Village by trying to capture the extent of community awareness to educate their children. Apart from that, it will examine the extent of Mandhala Senom's contribution to awareness of children's education. The qualitative method is used through a descriptive approach as a basis for describing and analyzing community participation using theory according to Theresia (2018) which consists of four indicators, namely participation in decision making, participation in implementing activities, participation in enjoying the results, participation in evaluation. Furthermore, the problem of community participation in the development of out-of-school education was identified by conducting in-depth interviews with Mandhala Senom Volunteers and the surrounding community, especially in East Barurambat. Based on the results of the research and discussion, it can be concluded that community participation is going well.